Negative electrode active material and lithium secondary battery comprising the same

By using lithium-titanium composites as the negative electrode active material, the problem of high charge transfer resistance of lithium secondary batteries at low temperatures is solved, and the low resistance and improved output characteristics are achieved under low temperature conditions, which are suitable for a variety of battery applications.

CN113950760BActive Publication Date: 2025-02-14LG ENERGY SOLUTION LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202080018614.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-06
Filing Date
2020-03-06
Publication Date
2025-02-14
Estimated Expiration
2040-03-06

AI Technical Summary

Technical Problem

The existing lithium titanium oxide negative electrode materials cannot effectively reduce the charge transfer resistance at low temperatures, resulting in poor output characteristics of lithium secondary batteries under low temperature conditions.

Method used

An anode active material containing a lithium titanium composite consisting of lithium titanium oxide, doped Zr and aluminum and sulfur-containing compounds coated on the surface, and the average particle size of the primary particles is controlled from 550 nm to 1.1. Between μm.

Benefits of technology

By optimizing the structure and composition of lithium-titanium composites, the charge transfer resistance is significantly reduced. Especially at low temperatures, the output characteristics of lithium secondary batteries are improved, and are suitable for 12V or 48V secondary battery systems and high-output automotive batteries. application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113950760B_ABST
    Figure CN113950760B_ABST
Patent Text Reader

Abstract

A negative electrode active material for a secondary battery is proposed, comprising a lithium-titanium composite, the lithium-titanium composite comprising a lithium titanium oxide represented by Chemical Formula 1; Zr doped into the lithium titanium oxide; and an Al sulfur compound coated on the surface of the lithium titanium oxide, wherein the lithium-titanium composite comprises a single primary particle or a mixture of a primary particle and a secondary particle formed by agglomeration of a plurality of the primary particles, wherein the average particle size of the primary particles of the lithium-titanium composite is 550 nm to 1.1 μm: [Chemical Formula 1] Li x Ti y O z , in Chemical Formula 1, x, y and z satisfy 0.1≤x≤4, 1≤y≤5 and 2≤z≤12.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a negative electrode active material and a lithium secondary battery including the negative electrode active material, and more particularly, to a negative electrode active material that can be used for a negative electrode having a reduced charge transfer resistance (CTR) at low temperatures and a lithium secondary battery including the negative electrode active material, the lithium secondary battery having low resistance at room temperature and low temperatures and having improved output characteristics.

[0002] This application claims priority to Korean Patent Application No. 10-2019-0025997 filed in Korea on March 6, 2019, the disclosure of which is incorporated herein by reference. Background Art

[0003] With the increasing energy costs due to the depletion of fossil energy and the growing concerns about environmental pollution, the need for eco-friendly alternative energy is a basic prerequisite for future living.

[0004] As the application fields of electrochemical devices have expanded to power sources for mobile phones, camcorders, portable computers, and even electric vehicles, much effort has been invested in the research and development of electrochemical devices.

[0005] In this regard, electrochemical devices have received more attention, and in particular, the development of rechargeable secondary batteries has been the focus of attention, and recently in the development of batteries, new electrode and battery designs for improving capacity density and specific energy have been studied and developed.

[0006] In particular, in recent years, lithium secondary batteries are used as power sources for electric vehicles (EV), hybrid electric vehicles (HEV), and micro-hybrid electric vehicles (u-HEV), and their application range is expanded to auxiliary power sources through a grid.

[0007] Micro hybrid electric vehicles partially use secondary batteries, and development of 12V dual or 48V secondary batteries for micro hybrid electric vehicles is toward higher output performance.

[0008] On the other hand, lithium titanium oxide provides an efficiency close to 100% in the first charge and discharge cycle, and due to its high driving voltage, does not form a film on the negative electrode surface by electrolyte decomposition reaction, so the application of lithium titanium oxide as a high-output negative electrode material is expected.

[0009] Therefore, in order to achieve fast charging and discharging characteristics above 20C, the use of lithium titanium oxide is necessary, but the existing lithium titanium oxide cannot meet the corresponding output requirements.

[0010] Therefore, there is still a need to develop lithium titanium oxide negative electrode materials for use in hybrid electric vehicle applications requiring high output characteristics. Summary of the invention

[0011] Technical issues

[0012] Therefore, the present disclosure aims to provide a negative electrode active material that can be used for a negative electrode having reduced charge transfer resistance at low temperatures.

[0013] The present disclosure also aims to provide a lithium secondary battery comprising the negative electrode active material.

[0014] Technical Solution

[0015] In order to solve the above problems, according to one aspect of the present disclosure, a negative electrode active material of the following embodiments is provided.

[0016] According to a first embodiment, there is provided a negative electrode active material for a secondary battery, comprising:

[0017] A lithium-titanium composite, comprising:

[0018] Lithium titanium oxide represented by the following Chemical Formula 1;

[0019] Zr doped into the lithium titanium oxide; and

[0020] a compound containing aluminum and sulfur coated on the surface of the lithium titanium oxide,

[0021] The lithium-titanium composite comprises a single primary particle or a combination of a primary particle and a secondary particle formed by agglomeration of the primary particles, and

[0022] The average particle size of the primary particles of the lithium-titanium composite is 550 nm to 1.1 μm:

[0023] [Chemical formula 1]

[0024] Li x Ti y O z

[0025] Where x, y and z satisfy 0.1≤x≤4, 1≤y≤5 and 2≤z≤12.

[0026] According to a second embodiment, in the first embodiment, the compound containing aluminum and sulfur may include Al2(SO4)3, Al2S3 or a combination thereof.

[0027] According to a third embodiment, in the first or second embodiment, the amount of the doped Zr may be 500 to 2,000 ppm based on the weight of the lithium titanium oxide.

[0028] According to a fourth embodiment, in any one of the first to third embodiments, the aluminum and sulfur-containing compound may be present in an amount of 0.4 mM to 0.9 mM based on 1 M lithium titanium oxide.

[0029] According to a fifth embodiment, in any one of the first to fourth embodiments, the lithium titanium oxide may be further doped with Al, S (sulfur), or both.

[0030] According to a sixth embodiment, in any one of the first to fifth embodiments, the average particle diameter of primary particles of the lithium-titanium based composite may be 600 nm to 1.0 μm.

[0031] In order to solve the above-mentioned problems, according to one aspect of the present disclosure, a method of manufacturing a negative electrode active material according to the following embodiments is provided.

[0032] According to a seventh embodiment, there is provided a method for manufacturing a negative electrode active material for a secondary battery, comprising:

[0033] (a) mixing a lithium precursor, a titanium precursor and a zirconium precursor to prepare a precursor mixture;

[0034] (b) heat-treating the precursor mixture at 700 to 1,100° C. to obtain lithium titanium oxide; and

[0035] (c) mixing the lithium titanium oxide obtained after the heat treatment with a compound containing aluminum and sulfur, and heat-treating the mixture at 400 to 500° C. to obtain a lithium titanium composite,

[0036] wherein the lithium-titanium composite comprises a single primary particle or a combination of a primary particle and a secondary particle formed by agglomeration of the primary particles; and

[0037] The average particle size of primary particles of the lithium-titanium composite is 550 nm to 1.1 μm.

[0038] According to an eighth embodiment, in the seventh embodiment, the lithium precursor may include Li2CO3, LiOH, LiF, Li2SO4, LiNO3, LiCl, or a combination thereof.

[0039] According to a ninth embodiment, in the seventh or eighth embodiment, the titanium precursor may include TiO2, TiCl4, TiOCl2, TiOSO4, TiO(OH)2, or a combination thereof.

[0040] According to a tenth embodiment, in any one of the seventh to ninth embodiments, the zirconium precursor may include Zr(OH) 4 , ZrO 2 , or a combination thereof.

[0041] According to an eleventh embodiment, in any one of the eighth to tenth embodiments, preparing the precursor mixture includes mixing the titanium precursor and the zirconium precursor with water, wet milling at 500 to 2,000 rpm for 30 minutes to 3 hours, and adding a lithium precursor.

[0042] According to a twelfth embodiment, in any one of the eighth to eleventh embodiments, the compound containing aluminum and sulfur may include Al2(SO4)3, Al2S3, or a combination thereof.

[0043] According to a thirteenth embodiment, in any one of the eighth to twelfth embodiments, the temperature of the heat treatment performed after mixing the lithium titanium oxide with the aluminum and sulfur-containing compound may be 400 to 480° C., and the aluminum and sulfur-containing compound may be present in an amount of 0.5 to 0.8 mM based on 1 M of the lithium titanium oxide.

[0044] According to a fourteenth embodiment, in the thirteenth embodiment, the heat treatment temperature may be 450° C., and the compound containing aluminum and sulfur may be present in an amount of 0.7 mM based on 1 M lithium titanium oxide.

[0045] In order to solve the above problems, according to one aspect of the present disclosure, a lithium secondary battery of the following embodiments is provided.

[0046] According to a fifteenth embodiment, there is provided a lithium secondary battery, comprising:

[0047] a positive electrode comprising a positive electrode active material, a negative electrode comprising a negative electrode active material, a separator interposed between the positive electrode and the negative electrode, and an electrolyte,

[0048] The negative electrode active material is the negative electrode active material for a secondary battery as defined in any one of the first to sixth embodiments.

[0049] Beneficial Effects

[0050] The negative electrode active material according to one embodiment of the present disclosure includes a lithium-titanium based composite, which includes a compound containing aluminum and sulfur coated on the surface of lithium titanium oxide, so that lithium ions do not occupy the 8a site during high-rate insertion, thereby having no kinetic effect, thereby minimizing the resistance increase rate accompanying the increase in the charge rate.

[0051] In addition, the negative active material according to one embodiment of the present disclosure has an optimal average particle size of primary particles of the lithium-titanium based composite, whereby a secondary battery employing the negative active material may have minimized charge transfer resistance and improved resistance at low temperatures.

[0052] As a result, the negative electrode active material according to one embodiment of the present disclosure may be used in 12V or 48V secondary battery system applications.

[0053] In addition, the negative electrode active material according to one embodiment of the present disclosure may be used in automotive battery applications requiring high output, such as micro-hybrid batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] The accompanying drawings illustrate preferred embodiments of the present disclosure and, together with the above description, are used to provide a further understanding of the technical aspects of the present disclosure; therefore, the present disclosure should not be construed as being limited to the accompanying drawings.

[0055] Figure 1 Graph showing the resistance at SOC 50% when charging at a low temperature (-20°C) in Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0056] Hereinafter, the present disclosure will be described in detail. Before the description, the terms or words used in the specification and the appended claims should not be interpreted as limited to the general meaning and dictionary meaning, but on the basis of the principle that the inventor is allowed to appropriately define the terms to provide the best interpretation, based on the meaning and concept corresponding to the technical aspects of the present disclosure. Therefore, the description disclosed herein and the illustrations shown in the accompanying drawings are only the most preferred embodiments, and are not intended to fully describe the technical aspects of the present disclosure, so it should be understood that other equivalents and variations may be made thereto when filing an application.

[0057] Currently, in the manufacture of lithium secondary batteries, reducing the charge transfer resistance (Rct) is one of the important issues. When the charge transfer resistance is high, lithium ions are generally difficult to be inserted / released into / from the negative electrode.

[0058] Charge transfer resistance greatly affects the resistance of secondary batteries containing lithium titanium oxide as negative electrode active materials at low temperatures (e.g., -20°C). Since the charge transfer resistance comes from the conductive path, when lithium titanium oxide is designed to have a small particle size to improve output, the conductive path is difficult to form, resulting in an increase in charge transfer resistance. On the other hand, in order to minimize the charge transfer resistance, the particle size of lithium titanium oxide needs to be increased, but a very large particle size makes it difficult for lithium ions to diffuse.

[0059] The present disclosure aims to provide a negative electrode active material, in order to improve the resistance of a secondary battery containing lithium titanium oxide as the negative electrode active material at low temperature, the negative electrode active material comprises a lithium titanium composite, the lithium titanium composite comprises a predetermined amount of aluminum and sulfur-containing compounds coated on the surface of the lithium titanium oxide, and has an optimal average particle size of primary particles of the lithium titanium composite, so that lithium ions do not occupy 8a sites during high-rate insertion, thereby having no kinetic effect, thereby minimizing the resistance increase rate accompanying the increase in the charge rate, and a secondary battery comprising the negative electrode active material.

[0060] According to one aspect of the present disclosure, there is provided a negative electrode active material for a secondary battery, comprising:

[0061] A lithium-titanium composite, comprising:

[0062] Lithium titanium oxide (LTO) represented by the following Chemical Formula 1;

[0063] Zr doped into the lithium titanium oxide; and

[0064] a compound containing aluminum and sulfur coated on the surface of the lithium titanium oxide,

[0065] The lithium-titanium composite comprises a single primary particle or a combination of a primary particle and a secondary particle formed by agglomeration of the primary particles, and the average particle size of the primary particles of the lithium-titanium composite is 550 nm to 1.1 μm:

[0066] [Chemical formula 1]

[0067] Li x Ti y O z

[0068] Where x, y and z satisfy 0.1≤x≤4, 1≤y≤5 and 2≤z≤12.

[0069] Generally, the negative electrode for high-output secondary batteries as an alternative to carbon-based negative electrodes is a negative electrode using lithium titanium oxide, which undergoes a two-phase reaction between a spinel structure and a rock salt structure by inserting and extracting lithium during charging and discharging. In this case, due to the two-phase reaction, even if the resistance is measured at the same SOC, the resistance value may vary depending on the direction (charging or discharging) of the set SOC, and the resistance value may also vary depending on the charge rate.

[0070] The above-mentioned inconsistent resistance value is caused by the structural characteristics of lithium titanium oxide, namely, lithium ions are inserted and deintercalated through the phase change between the spinel structure and the salt rock structure, and this problem may make the estimation algorithm very complicated because when a lithium secondary battery using lithium titanium oxide as the negative electrode active material is used in a battery pack, the estimation in the battery management system (BMS) is difficult.

[0071] However, as in the present disclosure, by using a negative electrode active material comprising a lithium-titanium based composite comprising lithium titanium oxide; Zr doped into the lithium titanium oxide; and a compound containing aluminum and sulfur coated on the surface of the lithium titanium oxide, the measured resistance value is low and constant regardless of the direction of setting the SOC and the charge rate, thereby overcoming the inherent resistance difference caused by the structural characteristics of the lithium titanium oxide.

[0072] In the case of conventional lithium titanium oxide, most lithium ions embedded during charge and discharge are located at the 8a site, and their positions do not change reversibly, resulting in an increase in resistance.

[0073] The negative electrode active material containing a lithium-titanium composite of the present disclosure comprises a compound containing aluminum and sulfur coated on the surface of lithium titanium oxide to inhibit the reduction of the crystallite size, thereby forming an interdiffusion layer on the surface, which increases the energy of Li entering the 8a site, so that the lithium ions will not occupy the 8a tetrahedral site of the lithium titanium oxide during high-rate insertion. As a result, the position of the embedded lithium ions during charging and discharging can be reversibly changed, and the inherent resistance difference caused by the structural characteristics of lithium titanium oxide can be overcome. Since the kinetic effect is not shown, the negative electrode active material containing a lithium-titanium composite of the present disclosure can be easily used in 12V or 48V secondary battery system applications.

[0074] The lithium secondary battery according to the present disclosure, which overcomes the inherent resistance difference caused by structural characteristics, can have minimal resistance change, for example, 5% or less or 3% or less, regardless of the direction in which the resistance is measured within the range between SOC 5 and 100 during charge and discharge.

[0075] The lack of kinetic effects makes it easy to use in 12V or 48V secondary battery system applications. In this case, the kinetic effect is the resistance difference between the pulse resistance measured after Li insertion (charging) into LTO at a low rate and the pulse resistance after insertion (charging) at a high rate.

[0076] In detail, in this case, when the starting SOC is SOC(start) and the target SOC is SOC(target), the kinetic effect can be defined as the percentage difference between the 10C charging resistance measured after charging from SOC(start) to SOC(target-20) (SOC 20% lower than the target SOC(%)) at 1C and then charging to SOC(target) at 1C, and the 10C charging resistance measured after charging from SOC(start) to SOC(target-20) at 1C and then charging to SOC(target) at 10C.

[0077] The lithium titanium oxide may be, for example, Li 0.8 Ti 2.2 O4、Li 2.67 Ti 1.33 O4、Li 1.33 Ti 1.67 O4、Li 1.14 Ti 1.71 O4、Li4Ti5O 12 , LiTi2O4 and Li2TiO3, more specifically Li4Ti5O which has a small change in crystal structure during charge and discharge and has a good spinel structure 12 , Li 1.33 Ti 1.67 O4 or LiTi2O4. However, the lithium titanium oxide is not limited thereto.

[0078] In the negative electrode active material for secondary batteries according to the present disclosure, the lithium-titanium composite may be in the form of a single primary particle, or in the form of a combination of a primary particle and a secondary particle formed by agglomeration of the primary particles. Here, the primary particle refers to the smallest unit of particles constituting the lithium-titanium composite, and the secondary particle refers to a particle in the form of an agglomeration of a plurality of primary particles, such as 3 or more, or 3 to 5, or 3 to 4 primary particles.

[0079] In order to obtain a lithium titanium oxide exhibiting high output characteristics, it is necessary to reduce the particle size and crystallite size of primary particles of the lithium titanium-based composite.

[0080] When spaces are formed between primary particles of the lithium-titanium based composite and the primary particle size is reduced, the distance of Li ions in the particles is reduced and the reaction area of ​​Li ions is increased, resulting in a significant improvement in output characteristics.

[0081] The lithium-titanium based composite may have a grain size of 100 nm to 200 nm, specifically 110 nm to 180 nm, more specifically 140 nm to 160 nm.

[0082] When the grain size is less than 100 nm, a large number of grain boundaries are not conducive to the embedding of lithium ions and the charging characteristics of the battery may deteriorate, while when the grain size is greater than 200 nm, lithium ions have difficulty diffusing in the grains, resulting in increased resistance and reduced output.

[0083] The grain size of the lithium-titanium composite particles can be measured using the Rietveld refinement program Topaz. The grain size measurement method using the Topaz program may include a method commonly used in the technical field to which the present disclosure belongs.

[0084] In the lithium-titanium composite of the present disclosure, the lithium-titanium oxide is doped with Zr. The doped Zr is used to reduce resistance and thus improve rate characteristics, specifically, to increase the bulk lattice constant. Furthermore, the doped Zr prevents an increase in the kinetic effect value by coating the lattice constant on the surface with Al to control the kinetic effect.

[0085] Based on the weight of lithium titanium oxide, the amount of doped Zr can be 500 to 2,000 ppm, or 700 to 1,500 ppm, or 900 to 1,100 ppm. When the amount of doped Zr satisfies the above range, the lattice constant of the body structure can be increased and the change in resistance can be significantly reduced, thereby increasing the mobility of Li ions, thereby providing a lithium secondary battery with improved output characteristics.

[0086] The aluminum and sulfur-containing compound is coated on the surface of the lithium titanium oxide to suppress a decrease in the lattice constant on the surface and to form an interdiffusion layer, which prevents Li from occupying the 8a site during fast charging (Li insertion).

[0087] The aluminum and sulfur containing compound may include Al2(SO4)3, Al2S3 or a combination thereof.

[0088] The amount of the compound containing aluminum and sulfur coated on the surface of the lithium titanium oxide may be 0.4 mM to 0.9 mM, specifically 0.5 mM to 0.8 mM or 0.5 mM to 0.7 mM, based on 1 M of the lithium titanium oxide.

[0089] When the amount of the aluminum-and-sulfur-containing compound satisfies the above range, the problem faced when the amount of the aluminum-and-sulfur-containing compound is low, i.e., the interdiffusion layer is not fully formed and the kinetic effect cannot be reduced, can be prevented; and the problem faced when the amount of the aluminum-and-sulfur-containing compound is very high, i.e., the thickness of the interdiffusion layer increases and the thickness of the side reaction layer (coating) on ​​the surface increases, resulting in increased resistance and reduced capacity, can be prevented.

[0090] According to one embodiment of the present disclosure, the lithium titanium oxide may be further doped with Al, S (sulfur) or both. When the lithium titanium oxide is further doped with Al, S (sulfur) or both, the increase in the lattice constant on the surface is suppressed and the lattice constant of Li embedded in the 8a site from the surface is reduced, and Li cannot occupy the 8a site during high rate charging.

[0091] In this case, the amount of at least one of Al and S (sulfur) for further doping may be 500 to 1,500 ppm, or 700 to 1,300 ppm, or 900 to 1,100 ppm, based on the total weight of the lithium-titanium based composite.

[0092] In the present disclosure, the average particle size (by volume, D50) of the primary particles of the lithium-titanium complex can be 550nm to 1.1μm, specifically, 600nm to 1.0μm or 650nm to 750nm. When the average particle size of the primary particles of the lithium-titanium complex is less than 550nm, it is difficult to form a conductive path in the lithium-titanium complex, the charge transfer resistance increases, and lithium ions are not easy to embed / de-embed in the negative electrode containing the lithium-titanium complex, resulting in reduced output characteristics. When the average particle size of the primary particles of the lithium-titanium complex is greater than 1.1μm, lithium ions are difficult to diffuse in the negative electrode containing the lithium-titanium complex, resulting in reduced capacity and increased resistance.

[0093] In the present disclosure, the average particle size D50 of the primary particles of the lithium-titanium composite can be defined as the particle size corresponding to 50% of the total volume accumulated from the small particles. In the present disclosure, the average particle size D50 can be measured, for example, by electron microscope observation using a scanning electron microscope (SEM) or a field emission scanning electron microscope (FE-SEM) or a laser diffraction method. More specifically, when the average particle size D50 is measured using a laser diffraction method, the primary particles of the lithium-titanium composite can be dispersed in a dispersion medium and introduced into a commercially available laser diffraction particle size measuring instrument (e.g., Microtrac MT3000), and after ultrasonic irradiation at about 28 kHz at an output of 60 W, the average particle size D50 at 50% of the particle size distribution in the measuring instrument can be calculated.

[0094] When the average particle size of the primary particles of the lithium-titanium composite satisfies the above range, the particle density can be increased and the electrode processing can be improved. When the average particle size is too small, a large amount of conductive material is required, which makes it impossible to form an electrode, and when the average particle size is too large, the output may be reduced.

[0095] Each of the primary particles and the secondary particles may independently have a spherical or quasi-spherical shape, where the quasi-spherical shape has a 3-dimensional volume, includes an elliptical shape, and includes particles of all shapes, including amorphous particles having an indefinite shape.

[0096] In addition, in one embodiment of the present disclosure, the negative electrode active material layer has a pore structure having a plurality of pores. For example, the pore structure may be derived from at least one of the characteristics of the shapes of a plurality of lithium-titanium based composite particles as described below.

[0097] The secondary particles of the lithium-titanium composite have a porous structure in which pores are formed on the surface and in the body of the secondary particles by pores formed between the agglomerated primary particles. In addition, the primary particles of the lithium-titanium composite may have a porous structure in which a plurality of primary pores are formed on the surface and in the body of the particles. The pores are connected to one or more adjacent pores, thereby serving as channels through which the electrolyte moves. Therefore, the pores formed and connected to each other inside the particles serve as channels through which the electrolyte moves.

[0098] The lithium titanium oxide contained in the lithium titanium composite has a spinel structure and provides a 3-dimensional Li diffusion path, thereby being advantageous for fast charging and high output characteristics. In addition, the lithium titanium oxide maintains the original crystal structure during charging and discharging, thereby having high structural stability.

[0099] In addition, the lithium titanium oxide may have a capacity of 160 to 172 mAh / g, preferably 165 to 170 mAh / g, after lithiation.

[0100] In addition, the lithium titanium oxide may generate lithium carbonate as a by-product in an amount of 0.5 wt % or less or 0.2 wt % or less based on 100 wt % of the lithium titanium oxide.

[0101] According to one aspect of the present disclosure, there is provided a method for manufacturing a negative electrode active material for a secondary battery, the method comprising:

[0102] (a) mixing a lithium precursor, a titanium precursor and a zirconium precursor to prepare a precursor mixture;

[0103] (b) heat-treating the precursor mixture at 700 to 1,100° C. to obtain lithium titanium oxide; and

[0104] (c) mixing the lithium titanium oxide obtained after the heat treatment with a compound containing aluminum and sulfur, and heat-treating the mixture at 400 to 500° C. to obtain a lithium titanium composite,

[0105] wherein the lithium-titanium composite comprises a single primary particle or a combination of a primary particle and a secondary particle formed by agglomeration of the primary particles; and

[0106] The average particle size of primary particles of the lithium-titanium composite is 550 nm to 1.1 μm.

[0107] In detail, an example of a method of manufacturing a negative electrode active material for a secondary battery according to the present disclosure may be as follows.

[0108] First, (a) a lithium precursor, a titanium precursor, and a zirconium precursor are mixed to prepare a precursor mixture.

[0109] The mixing of the precursor mixture in step (a) is a process for uniformly mixing the lithium precursor, the titanium precursor and the zirconium precursor, and the mixing method is not limited to a specific type and may include any mixing method for uniformly mixing the precursor mixture in a dry state, and may include a wet mixing method and a dry mixing method.

[0110] The mixing may use a wet mixing method, for example, a wet mixing method using a spray drying process, where a lithium precursor, a titanium precursor, and a zirconium precursor are added to a solvent and stirred to uniformly mix them to prepare a precursor composition. The precursor composition may be injected into a chamber having a spray dryer, and then the solvent is evaporated to produce a mixed precursor powder.

[0111] In detail, the precursor composition can be prepared by dissolving a lithium precursor and a titanium precursor in a solvent to prepare a composition, and adding a zirconium precursor while stirring the composition, and the volatile solvent used may include water such as deionized water or distilled water, an alcohol having a small number of carbon atoms such as methanol, ethanol or propanol, or acetone, and any solvent that can be easily evaporated by heat applied during spray drying can be used.

[0112] According to one embodiment of the present disclosure, in the step of preparing the precursor mixture, the precursor may have a controlled average particle size in order to adjust the average particle size of the lithium titanium oxide subsequently obtained by sintering the precursor mixture to a desired level.

[0113] In detail, in the step of preparing the precursor mixture, the grinding time and rpm conditions can be adjusted to control the average particle size of the precursor. Therefore, the step of preparing the precursor mixture may include: mixing the titanium precursor and the zirconium precursor with water, wet milling at 500 to 2,000 rpm for 30 minutes to 3 hours, and mixing the wet milled result with the lithium precursor. In addition, the wet milling can be performed at 800 to 1,500 rpm for 1 to 2 hours, or at 500 to 1,000 rpm for 30 minutes to 80 minutes.

[0114] As described above, the prepared precursor composition may be injected into a chamber having a spray dryer, and the precursor composition may be sprayed by the spray dryer, and drying may be performed at the same time.

[0115] The spray dryer may include, for example, an ultrasonic spray dryer, an air nozzle spray dryer, an ultrasonic nozzle spray dryer, a filter expansion aerosol generator, an electrostatic spray dryer, or a combination thereof. Spray drying may preferably be performed at an internal chamber temperature of 20 to 300° C. When the temperature is higher than 300° C., the mixed precursor powder may agglomerate or grow particles, and thus appropriate temperature control is required.

[0116] The mixing may use a dry mixing method, and the dry mixing method may include mixing the lithium precursor, the titanium precursor, and the zirconium precursor by a mechanical method, for example, the mixing method may use a ball mill, a high-speed rotary mill, a stirring mill, a jet mill, or a combination thereof.

[0117] The lithium precursor is not limited to a specific type and may include any source material capable of supplying lithium, such as a lithium salt including lithium ions and a salt, for example, Li2CO3, LiOH, LiF, Li2SO4, LiNO3, LiCl, or a combination thereof.

[0118] In addition, the titanium precursor is not limited to a specific type and may include any type of source material capable of supplying titanium, such as titanium oxide, and the titanium precursor may be in the form of a hydrate and a dry powder. In this case, when the titanium precursor is a hydrate, it may be desirable to use a wet mixing method to mix the titanium precursor with a lithium precursor, and when the titanium precursor is a dry powder, it may be desirable to use a dry mixing method. The titanium precursor may include, for example, TiO2, TiCl4, TiOCl2, TiOSO4, TiO(OH)2, or a combination thereof.

[0119] The zirconium precursor may include Zr(OH)4, ZrO2, or a combination thereof.

[0120] Subsequently, (b) the precursor mixture is heat-treated at 700 to 1,100° C. to obtain lithium titanium oxide.

[0121] The step (b) may include heat treating the precursor mixture, and may be a sintering process for heat treating the mixed dry precursor powder by any method to produce lithium titanium oxide.

[0122] The heat treatment temperature or time may need to be appropriately controlled, and in terms of battery performance and safety, it may be necessary to prevent the lithium precursor, titanium precursor or zirconium precursor from remaining unreacted and avoid byproducts such as lithium salts generated by side reactions, and it may be necessary to control the sintering conditions.

[0123] The heat treatment is performed at a temperature of 700 to 1,100°C, or about 750 to 1050°C, or 790 to 1000°C.

[0124] When the heat treatment temperature is lower than 700°C and sufficient heat is not supplied, lithium salts such as unreacted lithium precursors or lithium compounds due to side reactions may remain in the lithium titanium oxide, and when there are a large amount of residual impurities, side reactions or gas generation may occur and affect the storage performance or output characteristics of the battery, and when the heat treatment temperature is higher than 1,100°C, lithium titanium oxide degradation or particle growth may occur due to excessive energy supply and affect the output characteristics of the battery. Therefore, it may be necessary to appropriately control the heat treatment temperature.

[0125] It may also be necessary to control the heat treatment time, and in the present disclosure, the heat treatment may preferably be performed for about 2 to 12 hours or 5 to 10 hours. When the heat treatment time is met, lithium titanium oxide having an optimal grain size and structural stability and a minimum amount of lithium byproducts can be produced, and unnecessary energy waste or process cost consumption can be avoided.

[0126] Subsequently, (c) the lithium titanium oxide obtained after the heat treatment is mixed with a compound containing aluminum and sulfur, and the mixture is heat-treated at 400 to 500° C. to obtain a lithium titanium-based composite.

[0127] The mixing of the lithium titanium oxide obtained after the heat treatment and the compound containing aluminum and sulfur may use, but is not limited to, any method generally used for forming a coating layer, and as described above, wet mixing or dry mixing may be used.

[0128] For example, a compound containing aluminum and sulfur may be mixed with a dispersion medium, and the mixture may be added to the lithium titanium oxide obtained after heat treatment, and stirred and mixed to prepare a composition. Subsequently, the prepared composition may be dried and placed in a chamber having, for example, a spray dryer, followed by solvent evaporation to prepare a mixed precursor powder. In this case, the spray dryer is as described above.

[0129] Subsequently, the dried resultant may be heat-treated at 400 to 500° C., or at 400 to 480° C., or 420 to 460° C. When the heat treatment temperature is outside the above conditions, coating cannot be achieved, or doping is performed without forming an interdiffusion layer, thereby failing to eliminate the kinetic effect or causing capacity reduction.

[0130] In addition, as described above, the compound containing aluminum and sulfur coated on the surface of the lithium titanium oxide may be present in an amount of 0.4 mM to 0.9 mM, specifically, 0.5 mM to 0.8 mM or 0.5 mM to 0.7 mM based on 1 M lithium titanium oxide.

[0131] In one embodiment of the present disclosure, the loading amount of the negative electrode active material on the negative electrode can be 0.2 mAh / cm 2 Up to 2mAh / cm 2 .

[0132] According to a specific embodiment of the present disclosure, the negative electrode active material layer may further include a binder resin and a conductive material. Here, the negative electrode active material layer may include a negative electrode active material: conductive material: binder resin in a weight ratio of 80 to 90:7 to 13:3 to 9.

[0133] In addition, in addition to the above-mentioned lithium titanium oxide, the negative electrode active material layer may also contain particles of at least one active material selected from the group consisting of carbonaceous materials commonly used as negative electrode active materials, such as natural graphite, artificial graphite; metals (Me), including Si, Sn, Li, Zn, Mg, Cd, Ce, Ni or Fe; alloys of metals (Me); oxides (MeOx) of metals (Me); and composites of metals (Me) and carbon as negative electrode active materials.

[0134] Non-limiting examples of the binder resin may include at least one selected from the group consisting of polyvinylidene fluoride-co-hexafluoropropylene, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), poly-N-vinyl pyrrolidone (PVP), styrene butadiene rubber (SBR), polyamide-imide and polyimide, but are not limited thereto.

[0135] The conductive material is not limited to a specific type and may include any electron conductive material that does not cause chemical changes, such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, Super-P black, carbon fiber, metal powder or metal fiber of copper, nickel, aluminum, silver.

[0136] In a specific embodiment of the present disclosure, the negative electrode can be manufactured by the following method. First, the negative electrode active material, the binder resin and the conductive material are dispersed in a suitable solvent to prepare a negative electrode slurry, the solvent is such as an organic solvent or water, the organic solvent is such as ethanol (EtOH), acetone, isopropanol, N-methylpyrrolidone (NMP) and propylene glycol (PG), the negative electrode slurry is pressed into an electrode shape, or the slurry is coated on a metal foil to form an electrode shape, or the negative electrode composition is rolled into a sheet state and attached to a metal foil to form an electrode, and the electrode-shaped formation is dried at a temperature of 100°C to 350°C to form a negative electrode. Describing the example of forming the negative electrode in more detail, the negative electrode slurry can be formed by pressing using a roll forming machine. The roll forming machine is designed to improve the electrode density and control the electrode thickness by pressing, and the roll forming machine includes an upper roller and a lower roller, a controller for controlling the roller thickness and the heating temperature, and a winding unit for winding and unwinding the electrode. The electrode wound into a roll form is pressed while passing through a roller press, and is wound into a roll form again to complete the electrode. In this case, the pressure applied by pressing is preferably 5 to 20 tons / cm 2 And the temperature of the roller is preferably 0 to 150°C. After the slurry is subjected to the rolling process, the slurry is dried. The drying process is carried out at a temperature of 100°C to 350°C, preferably 150°C to 300°C. In this case, when the drying temperature is lower than 100°C, the solvent is difficult to evaporate, and when the drying is carried out at a high temperature higher than 350°C, oxidation of the conductive material may occur. Therefore, preferably, the drying temperature is equal to or higher than 100°C and does not exceed 350°C. In addition, the drying process is preferably carried out at a temperature as described above for about 10 minutes to 6 hours. The drying process can keep the powder particles together while drying the shaped negative electrode composition (solvent evaporation), thereby improving the strength of the negative electrode.

[0137] The lithium secondary battery of the present disclosure includes the above-mentioned negative electrode and positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.

[0138] The positive electrode can be manufactured by bonding the positive electrode active material to the positive electrode current collector by conventional methods known in the art to which the present disclosure belongs. Non-limiting examples of the positive electrode active material may include positive electrode active materials commonly used in positive electrodes of electrochemical devices, and are preferably lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide or lithium composite oxide thereof. Non-limiting examples of the positive electrode current collector may include foil made of aluminum, nickel or a combination thereof.

[0139] The separator may include a single porous substrate having a plurality of pores, or a porous substrate in combination with a porous coating layer including inorganic particles and a binder polymer coated on at least one surface of the porous substrate.

[0140] The porous substrate may be a porous polymer substrate, specifically, a porous polymer film substrate or a porous polymer nonwoven fabric substrate.

[0141] The porous polymer film substrate may be a porous polymer film made of polyolefin such as polyethylene and polypropylene, and the polyolefin porous polymer film substrate exhibits a closed-cell function at a temperature of, for example, 80 to 130°C.

[0142] In addition, the porous polymer film substrate can be formed into the shape of a film using various types of polymers such as polyolefins and polyesters. In addition, the porous polymer film substrate can be formed by stacking more than two film layers, and each film layer can be formed by polymers such as polyolefins and polyesters as described above used alone or in combination.

[0143] In addition, in addition to the above-mentioned polyolefins, the porous polymer film substrate and the porous nonwoven fabric substrate may be formed of polyester, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether and polyphenylene sulfide, used alone or in combination. The thickness of the porous substrate is not particularly limited, but is preferably 1 to 100 μm, more preferably 5 to 50 μm, and the pore size and porosity of the porous substrate are not particularly limited, but the pore size is preferably 0.01 to 50 μm and the porosity is preferably 10% to 95%.

[0144] In the separator according to one aspect of the present disclosure, the binder polymer used to form the porous coating layer may include a polymer commonly used in the technical field to which the present disclosure belongs for forming the porous coating layer. In particular, the glass transition temperature T g The polymer is -200°C to 200°C to improve the mechanical properties of the finally formed porous coating layer, such as flexibility and elasticity. The binder polymer faithfully functions as a binder that connects and stably fixes the inorganic particles, helping to prevent the mechanical properties of the separator having the porous coating layer from deteriorating.

[0145] In addition, the binder polymer does not need to be able to transport ions, but the use of polymers that can transport ions can further improve the performance of the electrochemical device. Therefore, the binder polymer may include those binder polymers with as high a dielectric constant as possible. The degree of dissociation of the salt in the electrolyte depends on the dielectric constant of the electrolyte solvent, and as the dielectric constant of the binder polymer increases, the degree of dissociation of the salt in the electrolyte may increase. The dielectric constant of the binder polymer can be in the range of 1.0 to 100 (measurement frequency = 1kHz), and specifically 10 or more.

[0146] In addition to the above functions, the binder polymer can exhibit a high degree of swelling in the electrolyte by gelling when impregnated with the liquid electrolyte. Therefore, the solubility parameter (i.e., Hildebrand solubility parameter) of the binder polymer is between 15 and 45 MPa. 1 / 2 Between or between 15 and 25 MPa 1 / 2 Between or between 30 and 45 MPa 1 / 2 Therefore, hydrophilic polymers with polar groups can be used instead of hydrophobic polymers such as polyolefins. When the solubility parameter is lower than 15 MPa 1 / 2 and above 45MPa 1 / 2 When the binder polymer is used, it is possible that the binder polymer does not swell in conventional liquid electrolytes for batteries.

[0147] Non-limiting examples of the binder polymer may include polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan and carboxymethyl cellulose, but are not limited thereto.

[0148] The weight ratio of the inorganic particles to the binder polymer is, for example, preferably in the range of 50:50 to 99:1, more preferably in the range of 70:30 to 95:5. When the ratio of the inorganic particles to the binder polymer satisfies the above range, the decrease in the pore size and porosity of the formed coating layer due to the high content of the binder polymer and the decrease in the peeling resistance of the formed coating layer due to the low content of the binder polymer can be prevented.

[0149] In the porous coating layer, inorganic particles are stacked in a contacting manner such that the inorganic particles are held together by the binder polymer to form interstitial volumes therebetween, and the interstitial volumes are empty spaces that become pores.

[0150] That is, the binder polymer can bind the inorganic particles to keep them together, for example, the binder polymer adheres and fixes the inorganic particles. In addition, the interstitial volume between the inorganic particles is the empty space that becomes the pore of the porous coating, and they are the spaces defined by the inorganic particles that are substantially in surface contact in the structure formed by the close packing or dense packing of the inorganic particles.

[0151] The inorganic particles are selected from the group consisting of inorganic particles having a dielectric constant of about 5 or more, inorganic particles capable of transporting lithium ions, and combinations thereof.

[0152] According to one embodiment of the present disclosure, the electrolyte comprises a + B - Here, A + Contains alkali metal cations such as Li + 、Na + , K + or a combination thereof, preferably Li + Ion. B - Contains anions such as F - , Cl - Br - ,I - 、NO3 - 、BF4 - PF6 - 、N(CN)2 - 、SCN - 、ClO4 - 、AsF6 - CF3SO3 - 、(CF3SO2)2 - 、C(CF2SO2)3 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、(CF3CF2SO2)2N - 、(CF3SO2)2N - CF3SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - or a combination thereof. Preferably, the A + B- The salt of the structure is a lithium salt.

[0153] The A + B - The salt of the structure dissolves and dissociates in an organic solvent. Non-limiting examples of the organic solvent may include propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma-butyrolactone or a combination thereof.

[0154] The electrolyte injection can be performed in any suitable step of the battery manufacturing process according to the manufacturing process and the required performance of the final product. That is, the electrolyte injection can be applied before the battery assembly or in the last step of the battery assembly.

[0155] According to an aspect of the present disclosure, there are provided a battery module including a lithium secondary battery as a unit battery, and a battery pack including the battery module.

[0156] As described above, the lithium secondary battery of the present disclosure uses a lithium-titanium composite as a negative electrode active material to achieve improved output characteristics without actually causing a decrease in high temperature characteristics and battery capacity, and when the lithium secondary battery is used as a replacement or supplement for an automotive lead-acid battery, a battery pack with improved efficiency can be provided.

[0157] The battery pack may include lithium secondary batteries connected in series, or may include lithium secondary battery modules connected in series, each lithium secondary battery module including lithium secondary batteries connected in parallel.

[0158] The battery pack can be used as a power source for devices that require high temperature stability, long cycle characteristics, and high rate characteristics. For example, the device may include, but is not limited to, an electric tool that is driven and operated by power derived from an electric motor; a vehicle, including an electric vehicle (EV), a micro-hybrid electric vehicle (u-HEV), a hybrid electric vehicle (HEV), and a plug-in hybrid electric vehicle (PHEV); an electric two-wheeler, including an electric bicycle and an electric scooter; an electric golf cart; and an energy storage system.

[0159] Hereinafter, the present disclosure will be described in detail by means of embodiments. However, the embodiments of the present disclosure may be modified in many other forms, and the scope of the present disclosure should not be construed as being limited to the following embodiments. The embodiments of the present disclosure are provided to fully explain the present disclosure to those of ordinary skill in the art to which the present disclosure belongs.

[0160] Example 1

[0161] 20 parts by weight of TiO2 as a titanium precursor was mixed with 50 parts by weight of water, Zr(OH)4 as a zirconium precursor was added at a concentration of 1,000 ppm based on lithium titanium oxide, and the resultant was put into a ball mill (Laval Laboratories, planetary ball mill Pulverisette 5), in which 200 parts by weight of 0.7 mm zirconium oxide abrasive was added and wet milled at 1,000 rpm for 60 minutes. Subsequently, 7.4 parts by weight of Li2CO3 as a lithium precursor was added and stirred to prepare a precursor composition.

[0162] The prepared precursor composition was spray dried to obtain a secondary particle precursor, and the secondary particle precursor was heat-treated in a furnace at a temperature of 790° C. for 10 hours to obtain lithium titanium oxide (Li4Ti5O 12 ). 0.06 parts by weight of Al2(SO4)3 (based on 1M lithium titanium oxide (Li4Ti5O 12 ) corresponding to 0.7 mM) was added to 50 parts by weight of water, and 20 parts by weight of the previously obtained lithium titanium oxide (Li4Ti5O 12 ) and stirred to prepare a composition. Subsequently, spray drying was performed to obtain a powder, and the powder was heat-treated in a furnace at a temperature of 450° C. for 5 hours to prepare a lithium-titanium composite. In this case, the obtained lithium-titanium composite was a primary particle having an average particle size D50 of 700 nm. The prepared lithium-titanium composite contained an aluminum- and sulfur-containing compound coated on the surface of lithium titanium oxide, and the aluminum- and sulfur-containing compound was present in an amount of 0.7 mM based on 1 M lithium titanium oxide. The doping amount of Zr was 1,000 ppm based on the weight of the lithium titanium oxide.

[0163] 92 wt% of a synthetic lithium-titanium composite, 4 wt% of carbon black as a conductive material, and 4 wt% of polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent to prepare a negative electrode mixture slurry. The prepared negative electrode mixture slurry was coated on one surface of an aluminum (Al) film having a thickness of about 20 μm as a negative electrode current collector, and then dried and rolled to manufacture a negative electrode having an active material layer with a porosity of about 33%.

[0164] <Manufacturing of positive electrode>

[0165] 96 wt% of LiMn2O4 and Li(Ni 0.33 Co 0.33 Mn 0.33A mixture of 20 wt % of MgO2, 2 wt % of carbon black as a conductive material, and 2 wt % of polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent to prepare a positive electrode mixture slurry. The positive electrode mixture slurry was coated on one surface of an aluminum (Al) thin film having a thickness of about 20 μm as a positive electrode current collector, and then dried and rolled to manufacture a positive electrode.

[0166] <Manufacturing of lithium secondary batteries>

[0167] A lithium secondary battery was manufactured by a conventional method using the above-mentioned positive and negative electrodes together with a separator of a polypropylene / polyethylene / polypropylene (PP / PE / PP) three-layer structure, and then injected with an electrolyte containing 1M LiPF6 dissolved in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 30:70.

[0168] <Manufacturing of Half-Cell>

[0169] The half-cell was fabricated as follows.

[0170] 0.4 g of a binder solution (containing 5 wt % polyvinylidene fluoride (PVdF) dissolved in N-methylpyrrolidone (NMP)) was added to 0.98 g of the lithium titanium based composite prepared above and mechanically stirred to prepare a slurry (weight ratio of LTO-A:PVdF was 98:2).

[0171] The slurry was coated on an aluminum foil to a thickness of 90 μm, and dried at 120° C. in a vacuum to manufacture a negative electrode.

[0172] Subsequently, the negative electrode was wound into a circular shape with a diameter of 12 mm, and a 2032-type coin half-cell was manufactured using lithium metal (foil) as a counter electrode. In this case, the electrolyte used was a solution obtained by dissolving 1.3 M LiPF6 in a mixed solvent of ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate in a volume ratio of 3:5:2.

[0173] Example 2

[0174] A lithium-titanium based composite was prepared by the same method as in Example 1, except that wet milling was performed at 1,000 rpm for 80 minutes to obtain primary particles having an average particle size D50 of 600 nm when preparing the precursor composition.

[0175] A negative electrode and a secondary battery including the same were manufactured by the same method as in Example 1, except that the prepared lithium-titanium based composite was used.

[0176] Example 3

[0177] A lithium-titanium based composite was prepared by the same method as in Example 1, except that wet milling was performed at 500 rpm for 30 minutes to obtain primary particles having an average particle size D50 of 1,000 nm when preparing the precursor composition.

[0178] A negative electrode and a secondary battery including the same were manufactured by the same method as in Example 1, except that the prepared lithium-titanium based composite was used.

[0179] Comparative Example 1

[0180] A lithium-titanium based composite was prepared by the same method as in Example 1, except that wet milling was performed at 1,500 rpm for 120 minutes to obtain primary particles having an average particle size D50 of 500 nm when preparing the precursor composition.

[0181] A negative electrode and a secondary battery including the same were manufactured by the same method as in Example 1, except that the prepared lithium-titanium based composite was used.

[0182] Comparative Example 2

[0183] A lithium-titanium composite was prepared by the same method as in Example 1, except that wet milling was performed at 1,500 rpm for 180 minutes to obtain primary particles having an average particle size D50 of 200 nm when preparing the precursor composition.

[0184] A negative electrode and a secondary battery including the same were manufactured by the same method as in Example 1, except that the prepared lithium-titanium based composite was used.

[0185] Comparative Example 3

[0186] A lithium titanium composite was prepared by the same method as in Example 1, except that a TiO2 raw material having a size of 1.5 μm was wet-milled at 600 rpm for 30 minutes to obtain primary particles having an average particle size D50 of 1.2 μm when preparing the precursor composition.

[0187] A negative electrode and a secondary battery including the same were manufactured by the same method as in Example 1, except that the prepared lithium-titanium based composite was used.

[0188] Characteristic measurement

[0189] Average particle size D50 of primary particles of lithium-titanium composite

[0190] The average particle size D50 of the primary particles of the lithium-titanium composite is defined as the particle size corresponding to 50% of the total volume accumulated from the small particles. In order to determine the average particle size D50, the primary particles of the lithium-titanium composite prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were dispersed in a dispersion medium and introduced into a laser diffraction particle size measuring instrument (Microtrac MT 3000), and after ultrasonic irradiation at about 28 kHz at an output of 60 W, the average particle size D50 at 50% of the particle size distribution in the measuring instrument was calculated.

[0191] Charge transfer resistance (Rct)

[0192] For each secondary battery manufactured in Examples 1 to 3 and Comparative Examples 1 to 3, after the third cycle of charging at 25°C with CC / CV, 0.2C, 5mV, 0.005C cutoff and discharging at CC, 0.2C, 1.0V, it was charged to SOC 50% at 0.2C. The charge transfer resistance of the coin half-cell charged to SOC 50% was measured using electrochemical impedance spectroscopy (EIS). In this case, the charge transfer resistance was measured at a frequency set to 10 6 The Z' (ohm) measured by EIS was calculated using a fitting program and its values ​​are shown in Table 1 below.

[0193] Charging resistance at room temperature

[0194] For each secondary battery manufactured in Examples 1 to 3 and Comparative Examples 1 to 3, the internal resistance at room temperature was measured. The temperature of each secondary battery was adjusted to 25°C by storing each secondary battery in a chamber at 25°C for 3 hours, and then the resistance was measured at each SOC by a hybrid pulse power characteristic (HPPC) test. In this case, each secondary battery was charged from SOC 5% to SOC 95% for 10 seconds at 10C, left to stand for 1 hour, and then discharged from SOC 95% to SOC 5% at 10C for 10 seconds, and the charge / discharge resistance of the lithium secondary battery was measured at every 5% interval from SOC 5% to SOC 95%. The resistance measured at SOC 50% when charging at room temperature (25°C) is shown in Table 1 below.

[0195] Charging resistance at low temperature

[0196] For each secondary battery manufactured in Examples 1 to 3 and Comparative Examples 1 to 3, the internal resistance at low temperature was measured. The temperature of each secondary battery was adjusted to -20°C by storing each secondary battery in a -20°C chamber for 3 hours, and then the resistance was measured at each SOC by HPPC test. In this case, each secondary battery was charged from SOC 5% to SOC 95% at 5C for 10 seconds, left to stand for 1 hour, and then discharged from SOC 95% to SOC 5% at 5C for 10 seconds, and the charge / discharge resistance of the lithium secondary battery was measured at every 5% interval from SOC5% to SOC 95%. In the following Tables 1 and Figure 1 3 shows the resistance measured at SOC 50% when charging at low temperature (-20°C).

[0197]

Table 1

[0198]

[0199] Refer to Table 1 and Figure 1 It was found that compared with the secondary batteries of Comparative Examples 1 to 3 using lithium-titanium composites with a smaller or larger average particle size as the negative electrode active material, the secondary batteries of Examples 1 to 3 using lithium-titanium composites with an average particle size of 550nm to 1.1μm as the negative electrode active material had a smaller charge transfer resistance, a similar level of charging resistance at room temperature, but very low charging resistance at low temperature. The secondary battery of Comparative Example 3 showed very high internal resistance at room temperature, and its charging resistance at low temperature could not be measured.

[0200] From the above, it can be expected that the secondary batteries of Examples 1 to 3 have improved output characteristics at low temperatures by adjusting the average particle size of primary particles of the lithium-titanium based composite used as a negative electrode active material to a range between 550 nm and 1.1 μm.

Claims

1. A negative electrode active material for a lithium secondary battery, comprising: A lithium-titanium composite, comprising: Lithium titanium oxide represented by the following Chemical Formula 1; Zr doped into the lithium titanium oxide; and a compound containing aluminum and sulfur coated on the surface of the lithium titanium oxide, in, The lithium-titanium composite comprises a single primary particle or a combination of a primary particle and a secondary particle formed by agglomeration of the primary particles, and The average particle size of the primary particles of the lithium-titanium composite is 600 nm to 1.0 μm: [Chemical formula 1] Li x You y ON z where x, y and z satisfy 0.1≤x≤4, 1≤y≤5 and 2≤z≤12, The amount of the doped Zr is 500 to 2,000 ppm based on the weight of the lithium titanium oxide. 2 . The negative electrode active material for a lithium secondary battery according to claim 1 , wherein the compound containing aluminum and sulfur comprises Al 2 (SO 4 ) 3 , Al 2 S 3 or a combination thereof. 3 . The negative electrode active material for a lithium secondary battery according to claim 1 , wherein the compound containing aluminum and sulfur is present in an amount of 0.4 mM to 0.9 mM based on 1 M lithium titanium oxide. 4 . The negative electrode active material for a lithium secondary battery according to claim 1 , wherein the lithium titanium oxide is further doped with Al, S, or both.

5. A method for producing a negative electrode active material for a lithium secondary battery according to any one of claims 1 to 4, comprising: (a) mixing a lithium precursor, a titanium precursor and a zirconium precursor to prepare a precursor mixture; (b) heat-treating the precursor mixture at 700 to 1,100° C. to obtain lithium titanium oxide; and (c) mixing the lithium titanium oxide obtained after the heat treatment with a compound containing aluminum and sulfur, and heat-treating the mixture at 400 to 500° C. to obtain a lithium titanium composite, wherein the lithium-titanium composite comprises a single primary particle or a combination of a primary particle and a secondary particle formed by agglomeration of the primary particles; and The average particle size of the primary particles of the lithium-titanium composite is 600 nm to 1.0 μm. 6 . The method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 5 , wherein the lithium precursor comprises Li 2 CO 3 , LiOH, LiF, Li 2 SO 4 , LiNO 3 , LiCl or a combination thereof.

7. The method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 5, wherein the titanium precursor comprises TiO2, TiCl4, TiOCl2, TiOSO4, TiO(OH)2 or a combination thereof.

8. The method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 5, wherein the zirconium precursor comprises Zr(OH)4, ZrO2 or a combination thereof.

9. The method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 5, wherein preparing the precursor mixture comprises: The titanium precursor and the zirconium precursor are mixed with water, wet-milled at 500 to 2,000 rpm for 30 minutes to 3 hours, and a lithium precursor is added.

10. The method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 5, wherein the compound containing aluminum and sulfur comprises Al2(SO4)3, Al2S3 or a combination thereof.

11. The method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 5, wherein the temperature of the heat treatment performed after mixing the lithium titanium oxide with the aluminum and sulfur-containing compound is 400 to 480°C, and the aluminum and sulfur-containing compound is present in an amount of 0.5 to 0.8 mM based on 1 M of the lithium titanium oxide. 12 . The method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 11 , wherein the heat treatment temperature is 450° C., and the compound containing aluminum and sulfur is present in an amount of 0.7 mM based on 1 M lithium titanium oxide.

13. A lithium secondary battery comprising: a positive electrode comprising a positive electrode active material, a negative electrode comprising a negative electrode active material, a separator between the positive electrode and the negative electrode, and Electrolyte, in, The negative electrode active material is a negative electrode active material for a lithium secondary battery as defined in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Method and device for detecting velocity in MIMO radar including velocity ambiguity resolution

    KR1020190025997A

  • Negative active material, method of preparing same, and rechargeable lithium battering including same

    CN102024949A

  • Electrode assembly and lithium secondary battery including same

    CN104205463A

  • Lithium titanate powder for electrode of power storage device, active substance material, and power storage device using same.

    CN106415899A

  • Lithium secondary battery having improved output characteristics

    CN107210429A